Arts: Inspiration for Life (LEARNing Landscapes, 2008)
In this article, the author recounts her experience at Centauri Summer Arts Camp, which has been instrumental in fostering her personal, artistic and spiritual growth. She emphasizes the particular importance of openness, communication, friendship, understanding and acceptance.
Keywords: artistic; growth; openness; communication; friendship; understanding; acceptance